Spontaneous rectus sheath hematoma mimicking acute abdomen - Hanumappa, Harish Kumar; A V, Lloyson Benix (Indian Journal of Case Reports, 2018)
Rectus sheath hematoma has been described in the past due to various etiologies with varying degrees of severity. It is a rare cause of acute abdomen. Clinical presentation may vary from person to person and based on site of collection and source of bleeding. Various management options including surgical and non-surgical measures have been described and generally present with tenderness with a mass of varying size based on the duration and amount of bleeding. Here, we present the case of a 72-year-old female with acute abdomen on presentation, unstable vitals, and severe pallor. A tender mass over the left lower part of the abdomen was found, and on further evaluation with imaging, the patient was found to have a rectus sheath hematoma. The hematoma was successfully treated with the evacuation of the hematoma and ligation of the bleeding vessel.